The Impact of Tax Regulation Changes on the Business Sector - Irda , Agustin Kustiwi; Rajendra, Achmad Bagas Djuan; NS, Sudarynianto; Ferreira, Paulino Da Costa (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Changes in tax regulations in Indonesia, especially following the enactment of the Law on the Harmonization of Tax Regulations (HPP Law), have had a significant impact on the business sector. This study aims to identify and analyze business actors’ responses to tax policy changes using a descriptive qualitative approach through interviews and document studies. The findings highlight four main themes: increasing administrative burden and the need for HR adaptation, changes in business strategies in response to rate adjustments and fiscal incentives, regulatory uncertainty affecting the investment climate, and business actors’ perceptions of government policy effectiveness. MSMEs are the most vulnerable group due to limited resources and access to information. Although reforms such as digitalized reporting systems and incentives are seen positively, implementation still faces challenges in coordination and outreach. Therefore, inclusive transition policies and open dialogue between the government and businesses are necessary to create a fair, efficient, and growth-supportive tax system.